Effects of Inulin, Maltodextrin and Wheat Fiber as Fat Replacers on Quality and Sensory Characteristics of Turkish dry fermented sausage (Soudjouk) - A. Şanes Pişkin, H. Ilyasoglu, B. Bayram, K.N. Kasapoğlu, B. Özcelik (International Journal of Advanced Science and Technology, 2020)
In this study the effects of carbohydrate based fat replacers -inulin, maltodextrin and wheat fiber on quality characteristics of Turkish soudjouk (sucuk) were investigated. Fat replacers were added at concentration of 1.5% into low- and medium-fat soudjouk formulations. Both fat level and fat replacers were found to have significant effect on the moisture content, weight and cooking losses, TBARS values, as well as some textural characteristics of the samples (p<0.05). Fat reduction in the final products ranged from 22.5% to 42.2%. Treatment with different fat replacers and fat level did not affect overall acceptability and sensorial properties of the samples indicating a good acceptability. In regards to color properties, only L values significantly differed depending on the fat replacer (p<0.01). The lowest cooking and weight loss values and TBARS levels and the highest fat reduction (by 42.2%), overall acceptability scores were obtained with low-fat samples containing wheat fiber. Therefore, wheat fiber can be effectively used as a fat substitute in meat products allowing the manufacture of low-caloric soudjouks contributing to the nutritional value and health.